PENYIMPANGANAN PERILAKU REMAJA DI PERKOTAAN - Suwendri Ni Made; Sukiani Ni Ketut (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
Adolescents as the next generation have an important role in the development of the nation. On the other hand, they frequently face social problems. The socialization they make sometimes deviates from the values, the norms prevailing in the society. The problems of this study are what factors causing the behavioral deviation of the urban adolescent, what several of the behavioral deviation of the urban adolescent, and what efforts should be taken to overcome the behavioral deviation of the urban adolescent. This study aims to determine the factors causing the behavioral deviation of the urban adolescent, to know the several of the behavioral deviations of the urban adolescent, and to find out the efforts to overcome the behavioral deviation of the urban adolescent. The theoretical basis used in examining the problems is the theory of social control and labeling theory. This study used a qualitative method. The data source was obtained from library research. The data were analyzed with the qualitative descriptive presentation technique. The result of this study showed that the deviation of adolescent behavior in urban areas is increasing highly. Several of the behavioral deviation of the urban adolescent such as juvenile delinquency, drug abuse, brawl, drunkenness, and smoking. The motives are such as the failure of socialization, weak of social control (no controller), and labeling to someone who tends to identify himself as the one who does deviation by society.